Studies on the population number of waterfowls in Zhejing Province - LIU An-xing; CHEN Zheng-hai; DING Ping; SUN Meng-jun; DU Qun (浙江大学学报. 农业与生命科学版)
The population number, density and diversity of waterfowls in Zhejiang Province were surveyed from April 1997 to July 1999, with the systematic sampling, line transect and point count methods.7 orders, 13 families and 97 species of waterfowl with 53.6% winter visitors were recorded. Podiceps grisegena, Calidris minuta and Limicola falcinellus were found as new records in Zhejiang Province. About 92.6 × 104 individuals was estimated as the total number of waterfowls in Zhejiang based on the density survey. Among these waterfowls, the number of Calidris alpina was highest and there were 25 species that population number was more than 10 000 individuals. The population densities of waterfowls in the area of sea coast were higher than in the areas of continent and island. In sea coast area, there were 21 species that density was more than 1.0 ind./km2 and 5 species in island area. There was, however, no any species that density was over 1.0 ind./km2 in continent area. The intertidal mud wetlands on the coast of Zhejiang, particularly in the areas of Wenzhou Bay and Yueqing Bay were very important areas not only for Ptatalea minor to use as stopover sites, but also for Larus saundersi to use as wintering sites.